ЭФФЕКТИВНОЕ ИСПОЛЬЗОВАНИЕ РОЛЕВОЙ ИГРЫ В ФОРМИРОВАНИИ ИНОЯЗЫЧНОЙ КОМПЕТЕНЦИИ УЧАЩИХСЯ (Scientific journal of the Fergana State University, 2023)
The article deals with the current issues of using role-playing.